Sodium ferric vanadium phosphate pyrophosphate as well as preparation method and application thereof
By forming a cladding layer on the surface of sodium ferric pyrophosphate, including carbon, boron and nitrogen, the problem of insufficient conductivity and structural stability of the positive electrode material of sodium ion battery is solved, and the reversible capacity and rate performance of the battery are significantly improved. Suitable for efficient energy storage applications of sodium ion batteries.
Patent Information
- Application Number
- CN202411280850.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-17
AI Technical Summary
The existing sodium ion battery positive electrode material NaFePO4 has insufficient sodium ion migration channels, resulting in low electrochemical performance and low intrinsic electronic conductivity of Na4Fe3(PO4)2(P2O7), which affects the reversible capacity and rate performance of the battery.
Sodium ferric pyrophosphate (Na(10+6x)/3Fe(7-3x)/3V2x(PO4)(6x+4)/3(P2O7) is used as the positive electrode material of the battery, and a cladding layer is formed on its surface. It contains carbon, boron and nitrogen elements to improve conductivity and structural stability.
It significantly improves the reversible capacity, cycle performance and rate performance of the battery, enhances the electrochemical performance, and is suitable for efficient energy storage applications of sodium ion batteries.
Smart Images

Figure CN119143100A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to sodium vanadium iron phosphate pyrophosphate and a preparation method and application thereof, belonging to the technical field of secondary batteries. Background Art
[0002] The development of renewable energy such as solar energy, wind energy, and tidal energy is of great significance to the sustainable development of human society. However, considering the intermittent nature of these renewable energy sources during use, it is necessary to establish a smart grid with a large energy storage system to achieve efficient use of renewable energy. As sodium resources are widely distributed, sodium-ion batteries have the advantages of low cost and high abundance, and are widely regarded as a potential large-scale energy storage system.
[0003] At present, the commonly used positive electrode material for sodium ion batteries is NaFePO4. However, NaFePO4 does not have a sodium ion migration channel and exhibits low activity when used in sodium ion batteries, which is not conducive to the electrochemical performance of sodium ion batteries. In order to improve the electrochemical performance of sodium ion batteries, Na4Fe3(PO4)2(P2O7) came into being. Na4Fe3(PO4)2(P2O7) has P2O7 with strong electron induction ability. 4- , with a higher theoretical average operating voltage (3.0V vs.Na + / Na), and the material has a three-dimensional sodium ion transport channel, which is beneficial to improving the rate performance of the battery.
[0004] However, Na4Fe3(PO4)2(P2O 7) It is composed of Na2FeP2O7 and NaFePO4 with a molar ratio of 1:2. The presence of the inactive component NaFePO4 will reduce the reversible capacity of the positive electrode material; and Na4Fe3(PO4)2(P2O 7) The intrinsic electronic conductivity is low. Summary of the invention
[0005] The invention provides sodium vanadium iron pyrophosphate phosphate, which has excellent reversible capacity and conductivity.
[0006] The invention provides a preparation method for preparing the sodium vanadium iron phosphate pyrophosphate. The preparation method is simple to operate and suitable for wide promotion and application.
[0007] The present invention provides a battery, comprising the sodium vanadium iron phosphate pyrophosphate, and the battery has excellent cycle performance and rate performance.
[0008] The present invention provides sodium vanadium iron pyrophosphate, wherein the sodium vanadium iron pyrophosphate comprises a core and a coating layer coated on at least a portion of the surface of the core;
[0009] The molecular formula of the core is shown in Formula 1;
[0010] Na (10+6x) / 3 Fe (7-3x) / 3 V 2x (PO4) (6x+4) / 3 (P2O7) Formula 1;
[0011] Where x≥0.25;
[0012] The coating layer includes carbon, boron and nitrogen.
[0013] The sodium vanadium iron pyrophosphate phosphate as described above, wherein in the unit cell of the sodium vanadium iron pyrophosphate phosphate, the length of the a-axis is The length of the b axis is The length of the c-axis is
[0014] The sodium vanadium iron pyrophosphate as described above, wherein the mass percentage of the coating layer in the sodium vanadium iron pyrophosphate is 1.0-3.0wt%; and / or,
[0015] In the sodium ferrovanadium phosphate pyrophosphate, the mass percentage of carbon element is 1.0-2.8wt%, the mass percentage of boron element is 0.01-0.05wt%, and the mass percentage of nitrogen element is 0.2-1.2wt%.
[0016] The sodium vanadium iron pyrophosphate as described above, wherein the D50 of the secondary particles of the sodium vanadium iron pyrophosphate is 2-6 μm; and / or,
[0017] The particle size of the primary particles of the sodium ferrovanadium phosphate pyrophosphate is 50-550 nm; and / or,
[0018] The particle size distribution of the secondary particles of the sodium ferrovanadium phosphate pyrophosphate is 1.5-4.0, wherein the particle size distribution Span=(D90-D10) / D50.
[0019] The sodium vanadium iron pyrophosphate as described above, wherein the thickness of the coating layer in the sodium vanadium iron pyrophosphate is 1-5 nm; and / or,
[0020] The particle size of the core is 50-500nm.
[0021] The sodium vanadium iron pyrophosphate as described above, wherein the porosity of the sodium vanadium iron pyrophosphate is 5-11%.
[0022] The sodium vanadium iron pyrophosphate as described above, wherein the compacted density of the sodium vanadium iron pyrophosphate is 1.8-2.1 g / cm 3 and / or,
[0023] The specific surface area of the sodium vanadium iron phosphate pyrophosphate is 4-15m 2 / g.
[0024] The present invention provides another method for preparing the sodium ferrovanadium phosphate pyrophosphate as described above, which comprises the following steps:
[0025] The raw material system including a sodium source, an iron source, a vanadium source, a phosphorus source, and a carbon source is sequentially subjected to a spray drying process and a first sintering process to obtain an intermediate material;
[0026] The intermediate material, the nitrogen source and the boron source are subjected to ball milling treatment and a second sintering treatment to obtain sodium vanadium iron pyrophosphate.
[0027] The preparation method as described above, wherein the raw material system further includes a dispersant, and the dispersant includes polyvinyl alcohol; and / or,
[0028] The carbon source is polyvinyl pyrrolidone.
[0029] The preparation method as described above, wherein, in the spray drying process, the inlet temperature is 175-195°C, the outlet temperature is 90-95°C, and the flow rate is 20-40 mL / min; and / or,
[0030] In the ball milling process, the ball-to-material ratio is (10-100): (1-5), the rotation speed is 250-500 r / min, and the time is 3-8 h.
[0031] The preparation method as described above, wherein in the first sintering treatment, the temperature is 300-400° C. and the time is 2-4 hours; and / or,
[0032] And / or, in the second sintering treatment, the temperature is 500-550° C. and the time is 8-16 hours.
[0033] The present invention provides a battery, which comprises the sodium vanadium iron phosphate pyrophosphate as described above.
[0034] The sodium vanadium iron phosphate pyrophosphate of the present invention has a special composition and structure so that when it is applied to a battery, it can improve the electrochemical performance of the battery, for example, it can improve the cycle performance and rate performance of the battery.
[0035] The invention provides a method for preparing sodium vanadium iron pyrophosphate, which can prepare the sodium vanadium iron pyrophosphate. The preparation method is simple to operate and suitable for wide promotion and application.
[0036] The present invention provides a battery, comprising the above-mentioned sodium iron vanadium phosphate pyrophosphate, so the battery has excellent electrochemical properties, for example, excellent cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 The XRD pattern of sodium vanadium iron pyrophosphate in Example 1 of the present invention;
[0039] Figure 2 This is a surface SEM image of sodium ferrovanadium phosphate pyrophosphate according to Example 1 of the present invention;
[0040] Figure 3 This is a surface SEM image of sodium ferrovanadium phosphate pyrophosphate of Comparative Example 6 of the present invention at a magnification;
[0041] Figure 4 This is a cross-sectional SEM image of sodium ferrovanadium phosphate pyrophosphate of Comparative Example 6 of the present invention at another magnification;
[0042] Figure 5 This is a cross-sectional SEM image of sodium vanadium iron pyrophosphate of Comparative Example 6 of the present invention;
[0043] Figure 6 The first week charge and discharge curve of the battery of Example 1 of the present invention at a current density of 0.5C and a voltage window of 2-4.6V;
[0044] Figure 7 The first week charge and discharge curve of the battery of Example 1 of the present invention at a current density of 0.5C and a voltage window of 1.5-4.6V;
[0045] Figure 8 Example 1 at a current density of 50 mA g -1 , the first week charge and discharge curve under the voltage window of 0.01-2.8V;
[0046] Fig. 9 The cycle performance curves of the batteries of Example 1 and Comparative Example 3 of the present invention at a current density of 0.5C;
[0047] Fig.10 The battery of Example 1 of the present invention is subjected to a current density of 50 mA g -1 , Cyclic performance curve of 60 cycles in the voltage window of 0.01-2.8V;
[0048] Fig.11 The figure is a rate performance diagram of the battery of Example 1 of the present invention and Comparative Example 3;
[0049] Fig.12 This is a rate performance diagram of the batteries of Example 1 and Comparative Example 6 of the present invention. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] A first aspect of the present invention provides sodium vanadium iron phosphate pyrophosphate, comprising a core and a coating layer coated on at least a portion of the surface of the core;
[0052] The molecular formula of the core is shown in Formula 1;
[0053] Na (10+6x) / 3 Fe (7-3x) / 3 V 2x (PO4) (6x+4) / 3 (P2O7) Formula 1;
[0054] Where x≥0.25;
[0055] The coating layer includes carbon, boron and nitrogen.
[0056] In the present invention, the coating layer can be coated on the entire surface of the core, or can be coated on a part of the surface of the core. The coating layer includes carbon, boron and nitrogen; and the core is a compound including Na, Fe, V, P and O.
[0057] Among them, carbon element can improve the conductivity of sodium vanadium iron pyrophosphate, nitrogen element and boron element can improve the structure of the coating layer, limit the agglomeration and growth of sodium vanadium iron pyrophosphate particles, and increase the number of hole carriers, thereby improving the electronic conductivity of sodium vanadium iron pyrophosphate; at the same time, the coating layer including nitrogen element and boron element can further improve the stability of the coating layer because the carbon-nitrogen bond and carbon-boron bond are very stable, and form a more stable protective layer on the surface of the inner core, effectively reduce the side reaction between the inner core and the electrolyte, and effectively improve the cycle stability of sodium vanadium iron pyrophosphate; when the inner core includes V element, the inner core can be considered to include Na3V2(PO4)3, NaFePO4, Na2FeP2O7 and Na4Fe3(PO4)2(P2O7). Due to the introduction of high voltage Na3V2(PO4)3 in the inner core, the proportion of NaFePO4 in the inner core is reduced, which can improve the reversible capacity and average working voltage of sodium vanadium iron pyrophosphate; and when sodium vanadium iron pyrophosphate is used in a battery, V will occur during the charge and discharge process of the battery.3+ To V 4+ and / or V 3+ To V 5+ The redox reaction further improves the reversible capacity and average working voltage of sodium vanadium iron pyrophosphate. It is worth mentioning that the V element has a variety of valences, for example, +2, +3, +4, +5. The sodium vanadium iron pyrophosphate containing the V element can use the high chemical valence of V as the positive electrode, or the low chemical valence of V as the negative electrode. Therefore, the sodium vanadium iron pyrophosphate can be used to prepare a symmetrical full battery, which can not only reduce the production cost, but also increase the adaptability of the positive and negative electrode materials of the full battery.
[0058] In some embodiments, when x=1 / 3, the molecular formula of the inner core is Na4Fe2V 0.67 (PO4)2(P2O7), it can be considered that the core includes 1 mol of NaFePO4, 1 / 3 mol of Na3V2(PO4)3 and 1 mol of Na2FeP2O7. Compared with the existing Na4Fe3(PO4)2(P2O7) (including 1 mol of Na2FeP2O7 and 2 mol of NaFePO4), the content of NaFePO4 in the core is significantly reduced, which helps to improve the reversible capacity and average working voltage of sodium vanadium iron pyrophosphate.
[0059] In some embodiments of the present invention, in the unit cell of sodium vanadium iron phosphate pyrophosphate, the length of the a-axis is The length of the b axis is The length of the c-axis is
[0060] In the present invention, the XRD spectrum of sodium ferrovanadium phosphate pyrophosphate can be obtained, and the XRD spectrum of sodium ferrovanadium phosphate pyrophosphate is refined to obtain the a-axis length, b-axis length and c-axis length of the unit cell of sodium ferrovanadium phosphate pyrophosphate.
[0061] In the present invention, the sodium vanadium iron phosphate pyrophosphate that meets the above-mentioned unit cell parameters has excellent structural stability and is not prone to collapse during the charge and discharge process of the battery, which is helpful for the cycle performance of the modified battery.
[0062] In some embodiments of the present invention, when the mass percentage of the coating layer in the sodium vanadium iron pyrophosphate is 1.0-3.0wt%, the coating layer can more fully protect the core while ensuring the electrochemical performance of the sodium vanadium iron pyrophosphate, thereby improving the stability of the sodium vanadium iron pyrophosphate. Further, in the sodium vanadium iron pyrophosphate, the mass percentage of the coating layer is 1.5-2.2wt%.
[0063] In some embodiments of the present invention, in the sodium vanadium iron pyrophosphate, the mass percentage of carbon element is 1.0-2.8wt%, the mass percentage of boron element is 0.01-0.05wt%, and the mass percentage of nitrogen element is 0.2-1.2wt%.
[0064] When the content of boron in sodium vanadium iron pyrophosphate meets the above range, boron is not easy to form an impurity phase sodium borate with sodium ions, which can ensure the phase purity of sodium vanadium iron pyrophosphate, improve the discharge specific capacity of sodium vanadium iron phosphate, and boron can form enough electron carriers in the coating layer to improve the electronic conductivity of sodium vanadium iron pyrophosphate; when the content of nitrogen in sodium vanadium iron pyrophosphate meets the above range, it can form enough active sites in the coating layer without affecting the microstructure of the coating layer and the diffusion path of sodium ions (ensuring the electronic conductivity and rate performance of sodium vanadium iron pyrophosphate), and improve the electrochemical performance of sodium vanadium iron pyrophosphate. Further, when the content of carbon, nitrogen and boron in sodium vanadium iron pyrophosphate is within the above range, each element can better cooperate to improve the reversible capacity, cycle stability and rate performance of the battery.
[0065] Furthermore, in the sodium vanadium iron pyrophosphate, the mass percentage of carbon element is 1.5-1.8wt%, the mass percentage of boron element is 0.015-0.03wt%, and the mass percentage of nitrogen element is 0.3-1.0wt%.
[0066] In some embodiments, an XRD pattern of sodium ferrovanadium phosphate pyrophosphate can be obtained, and the XRD pattern of sodium ferrovanadium phosphate pyrophosphate can be refined to obtain Rw and Rp, and the phase purity of sodium ferrovanadium phosphate pyrophosphate can be determined according to Rw and Rp. In a specific embodiment, Rw is 4.57% and Rp is 3.65% obtained by XRD refinement, indicating that the phase purity of the sodium ferrovanadium phosphate pyrophosphate is higher.
[0067] In some embodiments of the present invention, the primary particles of sodium vanadium iron pyrophosphate have a particle size of 50-550 nm.
[0068] In the present invention, the primary particles of sodium ferrous vanadium phosphate pyrophosphate refer to sodium ferrous vanadium phosphate pyrophosphate that has not been agglomerated. When the particle size of the primary particles of sodium ferrous vanadium phosphate pyrophosphate meets the above range, the sodium ferrous vanadium phosphate pyrophosphate can be prevented from being broken during long-term use while ensuring the ion deintercalation efficiency of the sodium ferrous vanadium phosphate pyrophosphate, thereby improving the compaction density of the sodium ferrous vanadium phosphate pyrophosphate, and thus improving the energy density, rate performance and cycle performance of the battery.
[0069] Furthermore, the D50 of the secondary particles of sodium vanadium iron pyrophosphate is 2-6 μm.
[0070] Among them, the secondary particles of sodium ferrovanadium phosphate pyrophosphate refer to large particles of sodium ferrovanadium phosphate pyrophosphate formed by agglomeration of primary particles. When the particle size of the secondary particles of sodium ferrovanadium phosphate pyrophosphate meets the above range, the sodium ferrovanadium phosphate pyrophosphate has excellent ion insertion and extraction efficiency and service life, and can improve the energy density, rate performance and cycle performance of the battery.
[0071] The inventors also found that when the particle size distribution of the secondary particles of sodium vanadium iron pyrophosphate is 1.5-4.0, where the particle size distribution Span = (D90-D10) / D50, the sodium vanadium iron pyrophosphate can further improve the cycle performance of the battery when applied to the battery.
[0072] In some embodiments of the present invention, in the sodium vanadium iron phosphate pyrophosphate, the thickness of the coating layer is 1-5 nm; and / or,
[0073] The particle size of the core is 50-500nm, and the obtained sodium vanadium iron phosphate pyrophosphate can be evenly mixed with a conductive agent when used in a battery, thereby improving the wettability of the electrolyte and shortening the transmission distance of sodium ions, thereby improving the electrochemical performance of the battery. Further, the particle size of the core is 50-300nm.
[0074] In some embodiments of the present invention, when the porosity of sodium vanadium iron pyrophosphate is 5-11%, the sodium vanadium iron pyrophosphate has excellent ion insertion and extraction efficiency when applied to batteries, and has excellent compaction density, which helps to improve the energy density of the battery.
[0075] The inventors also found that when the compacted density of sodium vanadium iron pyrophosphate is 1.8-2.1 g / cm 3 When the sodium vanadium iron pyrophosphate is used in a battery, the energy density and rate performance of the battery can be further improved. In some embodiments, the compacted density of the sodium vanadium iron pyrophosphate is ≥ 2.08 g / cm 3 .
[0076] Furthermore, when the specific surface area of sodium vanadium iron pyrophosphate is 4-15m 2 / g, the sodium vanadium ferrophosphate pyrophosphate can react more fully with the electrolyte while reducing the side reaction between the sodium vanadium ferrophosphate pyrophosphate and the electrolyte, thereby improving the electrochemical performance of the battery.
[0077] The second aspect of the present invention provides a method for preparing the sodium vanadium iron phosphate pyrophosphate of the first aspect, comprising the following steps: spray drying a raw material system including a sodium source, an iron source, a vanadium source, a phosphorus source, and a carbon source and performing a first sintering treatment in sequence to obtain an intermediate material;
[0078] The intermediate material, the nitrogen source and the boron source are subjected to ball milling treatment and a second sintering treatment to obtain sodium vanadium iron pyrophosphate.
[0079] Specifically, a sodium source, an iron source, a vanadium source, a phosphorus source, and a carbon source with specific contents are mixed to form a first raw material system, the first raw material system is spray-dried to obtain spray particles, and then the spray particles are subjected to a first sintering treatment to remove organic components in the spray particles, thereby obtaining an intermediate material including a core and a carbon layer covering at least a portion of the surface of the core, wherein the surface and pores of the intermediate material have large and numerous pores;
[0080] Then, the intermediate material, nitrogen source and boron source are ball-milled to break the intermediate material and reduce the porosity of the intermediate material, thereby obtaining a ball-milled material. Finally, the ball-milled material is subjected to a second sintering treatment to allow nitrogen and boron elements to enter the carbon layer to form a coating layer, and the coating layer is coated on at least part of the surface of the inner core, thereby obtaining sodium vanadium iron pyrophosphate.
[0081] The present invention does not particularly limit the sodium source, and the sodium source may be a compound containing sodium commonly used in the art. Exemplarily, the sodium source may be tetrasodium pyrophosphate; the present invention does not particularly limit the iron source, and the iron source may be a compound containing iron commonly used in the art. Exemplarily, the iron source may be ferric phosphate; the present invention does not particularly limit the vanadium source, and the vanadium source may be a compound containing vanadium commonly used in the art. Exemplarily, the vanadium source may be ammonium metavanadate; the present invention does not particularly limit the phosphorus source, and the phosphorus source may be a compound containing phosphorus commonly used in the art. Exemplarily, the phosphorus element may be tetrasodium pyrophosphate; the present invention does not particularly limit the carbon source, and the carbon source may be a compound that can form carbon after sintering commonly used in the art; the present invention does not particularly limit the boron source, and the boron source may be a compound containing boron commonly used in the art. Exemplarily, the boron source may be boric acid; the present invention does not particularly limit the unit, and it may be a compound containing nitrogen commonly used in the art. Exemplarily, the nitrogen source may be urea.
[0082] The preparation method of the present invention can prepare the sodium vanadium iron phosphate pyrophosphate of the first aspect. The preparation method is simple to operate and is suitable for wide promotion and application.
[0083] In some embodiments of the present invention, the raw material system further includes a dispersant, and the dispersant includes polyvinyl alcohol.
[0084] In the present invention, the dispersant can improve the dispersibility of the components in the raw material system, avoid the components from sticking to each other, and limit the growth of the particles of the intermediate material to obtain more spray particles, thereby increasing the yield of sodium ferrovanadium phosphate pyrophosphate.
[0085] Furthermore, when the carbon source is polyvinyl pyrrolidone (PVP), PVP can be adsorbed on the solid / liquid interface and coated on the surface of the core, isolating each core particle well during the high-temperature carbonization process, weakening the mutual adhesion between the core particles, and limiting the growth of the core particles. Not only can more spray particles be obtained, but also the carbon layer can be more evenly coated on the surface of the core, which helps to improve the electrochemical performance of sodium vanadium iron pyrophosphate. It is worth mentioning that using PVP as a carbon source, matching nitrogen and boron elements, can further improve the electronic conductivity of sodium vanadium iron pyrophosphate, thereby improving the electrochemical performance of the battery.
[0086] In the present invention, the process parameters of the spray drying treatment, the first sintering treatment, the ball milling treatment and the second sintering treatment can also be limited, so as to further improve the electrochemical performance of sodium vanadium iron pyrophosphate.
[0087] In some embodiments of the present invention, when the inlet temperature is 175-195°C, the outlet temperature is 90-95°C, and the flow rate is 20-40mL / min during the spray drying process, dry spray particles can be obtained more efficiently, which is helpful for the subsequent process and thus obtains sodium iron vanadium phosphate pyrophosphate with better electrochemical properties.
[0088] Furthermore, in the first sintering treatment, the temperature is 300-400° C. and the time is 2-4 hours, which helps to more efficiently and fully remove the organic components in the spray particles, so that the carbon layer is more evenly coated on at least part of the surface of the inner core to obtain an intermediate material.
[0089] In some embodiments of the present invention, when the ball-to-material ratio is (10-100): (1-5), the rotation speed is 250-500 r / min, and the time is 3-8 h during the ball milling process, the intermediate material can be more fully crushed, the porosity of the intermediate material can be reduced, and sodium vanadium iron pyrophosphate with a uniform coating layer and a low porosity can be obtained.
[0090] In some embodiments, the ball milling beads may include first ball milling beads, second ball milling beads and third ball milling beads, wherein the diameter of the first ball milling beads is 5 mm, the diameter of the second ball milling beads is 7 mm, the diameter of the third ball milling beads is 10 mm, and the mass ratio of the first ball milling beads, the second ball milling beads and the third ball milling beads can be 4:3:3.
[0091] Furthermore, in the second sintering treatment, the temperature is 500-550°C and the time is 8-16h, so that the boron element and the nitrogen element can more fully enter the carbon layer to form a coating layer, thereby obtaining sodium vanadium iron pyrophosphate with uniform coating and low porosity.
[0092] In some embodiments, the mass ratio of the intermediate material to the mass of the carbon source can be 100:(1-40), so that the mass percentage of the coating layer in the sodium vanadium iron pyrophosphate is 1.0-3.0 wt%.
[0093] In some embodiments, the mass of the carbon source, nitrogen source and boron source can be limited, wherein the mass ratio of the carbon source to the nitrogen source and the boron source is 1: (0.05-0.5): (0.01-0.05), so that the mass percentage of the carbon element in the sodium ferric pyrophosphate is 1.0-2.8wt%, the mass percentage of the boron element is 0.01-0.05wt%, and the mass percentage of the nitrogen element is 0.2-1.2wt%, so as to give full play to the role of the nitrogen and boron elements in the sodium ferric pyrophosphate and improve the electronic conductivity of the sodium ferric pyrophosphate.
[0094] A fourth aspect of the present invention provides a battery comprising the sodium vanadium iron phosphate pyrophosphate of the first aspect.
[0095] In the present invention, sodium vanadium iron phosphate pyrophosphate can be prepared into pole pieces using methods commonly used in the art, and then the pole pieces are assembled with metallic sodium to obtain a battery.
[0096] The battery of the present invention, because it includes the sodium vanadium iron phosphate pyrophosphate of the first aspect, has excellent rate performance and cycle performance.
[0097] The technical solution of the present invention will be further explained below in conjunction with specific embodiments.
[0098] Example 1
[0099] The battery of this embodiment is prepared by a method comprising the following steps:
[0100] 1. Preparation of pole piece
[0101] 1) Preparation of sodium vanadium iron phosphate pyrophosphate
[0102] a. Na4Fe2V 2 / 3 Based on the stoichiometric ratio of (PO4)2(P2O7), ferric phosphate, ammonium metavanadate, tetrasodium pyrophosphate, polyvinyl alcohol, polyvinyl pyrrolidone and deionized water are uniformly mixed to obtain a raw material system; the raw material system is then spray-dried to obtain spray particles; the spray particles are then first sintered in a tubular furnace filled with nitrogen to obtain an intermediate material including a core and a carbon layer located on at least a portion of the surface of the core;
[0103] Wherein, in the raw material system, the mass percentage of polyvinyl alcohol is 1%, and the mass percentage of polyvinyl pyrrolidone is 5%;
[0104] In the spray drying process, the inlet temperature was 185°C, the outlet temperature was 93°C, and the peristaltic pump flow rate was 35 ml / min;
[0105] In the first sintering treatment, the heating rate was 2°C / min, the temperature was 380°C, and the time was 4h;
[0106] b. ball-milling the intermediate material with urea and boric acid to obtain a ball-milled material; then, subjecting the ball-milled material to a second sintering treatment in a nitrogen-filled tubular furnace to obtain sodium vanadium iron pyrophosphate including a coating layer;
[0107] In the ball milling process, the ball-to-material ratio is 5:1, the rotation speed is 400 r / min, the time is 3 h, the ball milling beads include first ball milling beads, second ball milling beads and third ball milling beads, the diameter of the first ball milling beads is 5 mm, the diameter of the second ball milling beads is 7 mm, the diameter of the third ball milling beads is 10 mm, and the mass ratio of the first ball milling beads, the second ball milling beads and the third ball milling beads can be 4:3:3;
[0108] Based on the total mass of the intermediate material, urea and boric acid, the mass percentage of urea is 1.5%, and the mass percentage of boric acid is 0.03%;
[0109] The second sintering treatment includes a first sintering treatment and a second sintering treatment in sequence, wherein in the first sintering treatment, the heating rate is 3°C / min, the temperature is 170°C, and the time is 2h, and in the second sintering treatment, the temperature is 540°C, and the time is 12h;
[0110] Other parameters of sodium ferrovanadium phosphate pyrophosphate are shown in Table 1.
[0111] 2) Preparation of pole piece
[0112] The pole piece includes an aluminum foil and an active layer arranged on two functional surfaces of the aluminum foil;
[0113] The active layer includes the sodium vanadium iron pyrophosphate in step 1), a conductive agent SP, and a binder PVDF, wherein the mass ratio of the sodium vanadium iron pyrophosphate, the conductive agent SP, and the binder PVDF is 90:5:5.
[0114] 2. Preparation of batteries
[0115] Assemble the electrode, separator, metal sodium and NaPF6 electrolyte in step 2) into a CR2032 button battery;
[0116] In the NaPF6 electrolyte, the concentration of NaPF6 is 1 mol / L, the mass percentage of FEC is 5%, and the solvent is EC and DEC in a volume ratio of 1:1.
[0117] Example 2
[0118] The preparation method of the battery of this embodiment is basically the same as that of embodiment 1, except that:
[0119] 1. Preparation of pole piece
[0120] 1) Preparation of sodium vanadium iron phosphate pyrophosphate
[0121] a. With Na 3.83 Fe 2.08 V 0.5 (PO4) 1.83 The raw material system is prepared based on the stoichiometric ratio of (P2O7).
[0122] Example 3
[0123] The preparation method of the battery of this embodiment is basically the same as that of embodiment 1, except that:
[0124] 1. Preparation of pole piece
[0125] 1) Preparation of sodium vanadium iron phosphate pyrophosphate
[0126] a. With Na 4.33 Fe 1.83 V(PO4) 2.33 The raw material system is prepared based on the stoichiometric ratio of (P2O7).
[0127] Example 4
[0128] The preparation method of the battery of this embodiment is basically the same as that of embodiment 1, except that:
[0129] 1. Preparation of pole piece
[0130] 1) Preparation of sodium vanadium iron phosphate pyrophosphate
[0131] b. Based on the total mass of the intermediate material, urea and boric acid, the mass percentage of urea is 5%, and the mass percentage of boric acid is 0.05%.
[0132] Example 5
[0133] The preparation method of the battery of this embodiment is basically the same as that of embodiment 1, except that:
[0134] 1. Preparation of pole piece
[0135] 1) Preparation of sodium vanadium iron phosphate pyrophosphate
[0136] b. Based on the total mass of the intermediate material, urea and boric acid, the mass percentage of urea is 1.0%, and the mass percentage of boric acid is 0.02%.
[0137] Example 6
[0138] The preparation method of the battery of this embodiment is basically the same as that of embodiment 1, except that:
[0139] 1. Preparation of pole piece
[0140] 1) Preparation of sodium vanadium iron phosphate pyrophosphate
[0141] a. With Na 4.53 Fe 1.73 V 1.2 (PO4) 2.53 The raw material system is prepared based on the stoichiometric ratio of (P2O7).
[0142] Example 7
[0143] The preparation method of the battery of this embodiment is basically the same as that of embodiment 1, except that:
[0144] 1. Preparation of pole piece
[0145] 1) Preparation of sodium vanadium iron phosphate pyrophosphate
[0146] b. The intermediate material is ball-milled at a speed of 550 r / min for 4 h to obtain sodium iron pyrophosphate.
[0147] Example 8
[0148] The preparation method of the battery of this embodiment is basically the same as that of embodiment 1, except that:
[0149] 1. Preparation of pole piece
[0150] 1) Preparation of sodium vanadium iron phosphate pyrophosphate
[0151] a. In the raw material system, the mass percentage of polyvinyl alcohol is 1%, and the mass percentage of polyvinyl pyrrolidone is 8%;
[0152] b. Based on the total mass of the intermediate material, urea and boric acid, the mass percentage of urea is 8%, and the mass percentage of boric acid is 0.6%.
[0153] Example 9
[0154] The preparation method of the battery of this embodiment is basically the same as that of embodiment 1, except that:
[0155] 1. Preparation of pole piece
[0156] 1) Preparation of sodium vanadium iron phosphate pyrophosphate
[0157] b. The intermediate material is ball-milled at a speed of 200 r / min for 2 h to obtain sodium iron pyrophosphate.
[0158] Example 10
[0159] The preparation method of the battery of this embodiment is basically the same as that of embodiment 1, except that:
[0160] 1. Preparation of pole piece
[0161] 1) Preparation of sodium ferrovanadium phosphate pyrophosphate
[0162] b. Based on the total mass of the intermediate material, urea and boric acid, the mass percentage of urea is 10%, and the mass percentage of boric acid is 0.03%.
[0163] Comparative Example 1
[0164] The preparation method of the battery of this comparative example is basically the same as that of Example 1, except that:
[0165] 1. Preparation of pole piece
[0166] 1) Preparation of sodium ferrovanadium phosphate pyrophosphate
[0167] b. No boric acid was added during the ball milling process. Based on the total mass of the intermediate material and urea, the mass percentage of urea was 1.5%.
[0168] Comparative Example 2
[0169] The preparation method of the battery of this comparative example is basically the same as that of Example 1, except that:
[0170] 1. Preparation of pole piece
[0171] 1) Preparation of sodium ferrovanadium phosphate pyrophosphate
[0172] b. No urea was added during the ball milling process. Based on the total mass of the intermediate material and boric acid, the mass percentage of boric acid was 0.03%.
[0173] Comparative Example 3
[0174] The preparation method of the battery of this comparative example is basically the same as that of Example 1, except that:
[0175] 1. Preparation of pole piece
[0176] 1) Preparation of sodium ferrovanadium phosphate pyrophosphate
[0177] b. The intermediate material is ball-milled without adding urea and boric acid to obtain a ball-milled material; then the ball-milled material is subjected to a second sintering treatment in a tubular furnace filled with nitrogen to obtain sodium vanadium iron pyrophosphate including a coating layer that does not include nitrogen and boron elements.
[0178] Comparative Example 4
[0179] The preparation method of the battery of this comparative example is basically the same as that of Example 1, except that:
[0180] 1. Preparation of pole piece
[0181] 1) Preparation of sodium vanadium iron phosphate pyrophosphate
[0182] a. With Na 3.67 Fe 2.17 V 0.33 (PO4) 1.67 The stoichiometric ratio of (P2O7) is used as the basis for configuring the raw material system.
[0183] Comparative Example 5
[0184] The preparation method of the battery of this comparative example is basically the same as that of Example 1, except that:
[0185] 1. Preparation of pole piece
[0186] 1) Preparation of sodium vanadium iron phosphate pyrophosphate
[0187] a. With Na 3.55 Fe 2.22 V 0.22 (PO4) 1.56 The stoichiometric ratio of (P2O7) is used as the basis for configuring the raw material system.
[0188] Comparative Example 6
[0189] The preparation method of the battery of this comparative example is basically the same as that of Example 1, except that:
[0190] 1. Preparation of pole piece
[0191] 1) Preparation of sodium vanadium iron phosphate pyrophosphate
[0192] Sintering the spray particles to obtain sodium vanadium iron pyrophosphate including a core and a carbon coating layer;
[0193] During the sintering process, the heating rate is 3°C / min, the temperature is 540°C, and the time is 12h; and step b is no longer performed.
[0194] Comparative Example 7
[0195] The preparation method of the battery of this comparative example is basically the same as that of Example 1, except that:
[0196] a. Na4Fe2V 0.67Based on the stoichiometric ratio of (PO4)2(P2O7), ferric phosphate, ferric oxide, tetrasodium pyrophosphate, polyvinyl alcohol, polyvinyl pyrrolidone, urea, boric acid and deionized water are uniformly mixed to obtain a raw material system, the raw material system is spray-dried to obtain spray particles, the spray particles are sintered in a tubular furnace filled with nitrogen to obtain a sintered material, the sintered material is ball-milled to obtain sodium ferrovanadium pyrophosphate phosphate (the inner core of the sodium ferrovanadium pyrophosphate phosphate also includes nitrogen and phosphorus elements);
[0197] Among them, in the raw material system, the mass percentage of polyvinyl alcohol is 1%, the mass percentage of polyvinyl pyrrolidone is 5%, the mass percentage of urea is 1.5%, and the mass percentage of boric acid is 0.03%;
[0198] In the spray drying process, the inlet temperature was 170 °C, the outlet temperature was 90 °C, and the peristaltic pump flow rate was 30 ml / min;
[0199] During the ball milling process, the speed was 400 r / min and the time was 3 h;
[0200] During the sintering process, the heating rate is 2°C / min, the temperature is 540°C, and the time is 12h.
[0201] Performance Testing
[0202] The sodium iron vanadium phosphate pyrophosphate and the battery in the embodiment and the comparative example were respectively subjected to the following performance tests;
[0203] 1. XRD test
[0204] The sodium ferrous vanadium phosphate pyrophosphate in the embodiment and the comparative example was subjected to an XRD test to obtain the XRD spectrum of the sodium ferrous vanadium phosphate pyrophosphate, and the XRD spectrum was refined to obtain the unit cell a-axis parameter, b-axis parameter and c-axis parameter of the sodium ferrous vanadium phosphate pyrophosphate. The results are shown in Table 1.
[0205] Figure 1 is the XRD pattern of sodium vanadium iron pyrophosphate in Example 1 of the present invention, from Figure 1 It can be seen that the peak of the XRD spectrum is sharp, indicating that the sodium vanadium iron pyrophosphate has excellent crystallinity. And after XRD refinement, Rw is 4.57% and Rp is 3.65%, indicating that the sodium vanadium iron pyrophosphate has a higher phase purity.
[0206] 2. SEM test
[0207] SEM tests were performed on the sodium vanadium iron pyrophosphate of Example 1 and Comparative Example 6, respectively, and a surface SEM image of the sodium vanadium iron pyrophosphate of Example 1 was obtained, and a surface SEM image and a cross-sectional SEM image of the sodium vanadium iron pyrophosphate of Comparative Example 6 were obtained.
[0208] Figure 2 This is a surface SEM image of sodium ferrovanadium phosphate pyrophosphate according to Example 1 of the present invention; Figure 3 This is a surface SEM image of sodium ferrovanadium phosphate pyrophosphate of Comparative Example 6 of the present invention at a magnification; Figure 4 This is a surface SEM image of sodium vanadium iron pyrophosphate of Comparative Example 6 of the present invention at another magnification; Figure 5 This is a cross-sectional SEM image of sodium vanadium iron pyrophosphate of comparative example 6 of the present invention. Figure 2-5 It can be seen that the secondary particles of the sodium ferrous vanadium phosphate pyrophosphate in the embodiment of the present invention are broken into block materials of varying rules, and the secondary particles of the sodium ferrous vanadium phosphate pyrophosphate do not have large pores, which helps to improve the compaction density of the sodium ferrous vanadium phosphate; while the sodium ferrous vanadium phosphate in Comparative Example 6 has pores on the surface or the sodium ferrous vanadium phosphate is a hollow structure, and the secondary particles of the sodium ferrous vanadium phosphate have large pores, which is not conducive to the compaction density of the sodium ferrous vanadium phosphate.
[0209] 3. Porosity test
[0210] The cross-sectional SEM image of the sodium vanadium iron pyrophosphate was obtained by machine cutting. The SEM image was binarized by the image processing software ImageJ, and the pores and solid parts in the image were converted into black and white, where white represents pores and black represents solids. The porosity was calculated by calculating the ratio of the area of white pixels to the total image area. The results are shown in Table 1.
[0211] 4. Test of the mass percentage of the coating layer and the content of B element, N element and C element in the coating layer
[0212] Weigh the mass of sodium ferrovanadium phosphate pyrophosphate, soak the sodium ferrovanadium phosphate pyrophosphate in aqua regia containing concentrated nitric acid and concentrated hydrochloric acid in a volume ratio of 1:3 for 24 hours, then filter and dry, weigh the mass of the core, and calculate the mass percentage of the coating layer;
[0213] The sodium ferrovanadium phosphate pyrophosphate was tested by an X-ray photoelectron spectrometer (XPS) to obtain the XPS spectrum of the sodium ferrovanadium phosphate pyrophosphate. The boron, nitrogen and carbon peak areas were fitted according to the XPS spectrum and the mass percentages of the boron, nitrogen and carbon elements in the sodium ferrovanadium phosphate were calculated. The results are shown in Table 1.
[0214] 5. Primary particle size, core particle size and coating thickness test
[0215] Sodium vanadium iron pyrophosphate was placed in anhydrous ethanol and completely dispersed using ultrasound, and then the particle size was measured by SEM;
[0216] Sodium vanadium iron pyrophosphate was sintered in a muffle furnace at 400°C for 4 hours, and then ultrasonically dispersed in anhydrous ethanol to obtain a core, and the particle size of the core was measured by SEM.
[0217] The difference between the particle size of the primary particle and the particle size of the inner core is the thickness of the coating layer. The results are shown in Table 1.
[0218] 6. Secondary particle size and particle size distribution test
[0219] Sodium ferrovanadium pyrophosphate was placed in anhydrous ethanol and completely dispersed with ultrasound, and then placed in a laser particle size analyzer to measure the average particle size, D50, D10, and D90 of the sodium ferrovanadium pyrophosphate secondary particles. The particle size distribution Span = (D90-D10) / D50. The results are shown in Table 1.
[0220] 7. Compaction density test
[0221] The sodium vanadium iron phosphate pyrophosphate was dried to obtain a dried material; the dried material was filled into the entire cylindrical mold, and a press was used to apply pressure to 30 MPa and maintained for 2 minutes. At this time, the mass m0 of the dried material, the height L in the cylindrical mold, and the diameter D1 in the mold were measured. According to ρ=4m0 / πD1 2 The compacted density ρ was calculated by L and the results are shown in Table 1.
[0222] 8. Specific surface area test
[0223] The specific surface area of sodium vanadium iron pyrophosphate was tested by nitrogen adsorption method. The results are shown in Table 1.
[0224] 9. Charge and discharge performance
[0225] The assembled CR2032 button battery was placed in the Xinwei battery test system for constant current charge and discharge test at room temperature, with a voltage window of 1.5-4.6V and a current density of 0.5C. The discharge curve of the battery was obtained, and the charge and discharge specific capacity and average operating voltage of the battery were obtained according to the charge and discharge curve of the battery. The results are shown in Table 2.
[0226] The charge and discharge curves of sodium vanadium iron pyrophosphate were obtained with voltage windows of 1.5-4.6V and 2.0-4.6V and current density of 0.5C. Figure 6 The first week charge and discharge curve of the battery of Example 1 of the present invention at a current density of 0.5C and a voltage window of 2-4.6V; Figure 7 The first week charge and discharge curve of the battery of Example 1 of the present invention at a current density of 0.5C and a voltage window of 1.5-4.6V. Figure 6 and Figure 7 It can be seen that the battery in Example 1 of the present invention has V 4+ To V5+ The redox platform exists at a voltage of 1.7 V. 3+ To V 2+ The redox platform shows that the sodium vanadium iron pyrophosphate can give full play to the advantages of the existence of various valences of metallic vanadium when used in batteries, improve the efficiency of electron migration, and thus increase the capacity of the battery.
[0227] The voltage window is 0.01-2.8 V and the current density is 50 mA g -1 , obtain the charge and discharge curve of sodium vanadium iron pyrophosphate, Figure 8 Example 1 at a current density of 50 mA g -1 , the first week charge and discharge curve under the voltage window of 0.01-2.8V, from Figure 8 It can be seen that the material in Example 1 as the negative electrode has a charge-discharge capacity of 163 mAh g -1 .
[0228] 10. Cycle performance
[0229] The assembled CR2032 button battery was placed in the Xinwei battery test system for constant current charge and discharge test at room temperature. When the voltage window was 1.5-4.6V and the current density was 0.5C, the battery was cycled to obtain the capacity retention rate of the battery after 100 cycles. The results are shown in Table 2.
[0230] Fig. 9 The cycle performance curves of the batteries of Example 1 and Comparative Example 3 of the present invention at a current density of 0.5C. Fig. 9 It can be seen that compared with Comparative Example 3, the battery in Example 1 has better cycle stability, and its capacity retention rate after 100 cycles is as high as 92.5%.
[0231] The current density is 50 mA g in the voltage window of 0.01-2.8 V. -1 , obtain the cycle performance curve of the battery after 60 cycles.
[0232] Fig.10 The battery of Example 1 of the present invention is subjected to a current density of 50 mA g -1 , the cycle performance curve of 60 cycles under the voltage window of 0.01-2.8V, from Fig.10 It can be seen that the charge specific capacity of the sodium ferrous vanadium pyrophosphate in Example 1 shows an upward trend first. This is mainly because the sodium ferrous vanadium pyrophosphate is fully infiltrated and activated by the electrolyte during the first 20 charge and discharge processes. After 60 cycles, the capacity retention rate of the sodium ferrous vanadium pyrophosphate is 93.5%.
[0233] 11. Rate performance
[0234] The assembled CR2032 button battery was placed in the Xinwei battery test system for constant current charge and discharge test at room temperature, with a voltage window of 1.5-4.6V and a current density of 10C to obtain the battery's discharge specific capacity. The results are shown in Table 2.
[0235] When the voltage window is 1.5-4.6V and the current density is 0.2C, 0.5C, 1C, 2C, 3C, 5C, 10C, and 20C, the discharge specific capacity of the battery is obtained respectively. Fig.11 Figure 1 is a rate performance diagram of the battery of Example 1 and Comparative Example 3 of the present invention. Fig.11 It can be seen that compared with Comparative Example 3, the battery in Example 1 has a better rate performance. The discharge specific capacity of the battery at 0.2C, 0.5C, 1C, 2C, 3C, 5C, 10C and 20C is 138.8 mAh g -1 , 123.2mAh g -1 , 118.6mAh g -1 , 112.6mAh g -1 、105.8mAh g -1 、95.7mAh g -1 、85.2mAh g -1 、76.9mAh g -1 When the current density returns to 0.2C, the discharge capacity can reach 133.9mAh g -1 , indicating that the structure of the sodium vanadium iron pyrophosphate in Example 1 is not destroyed after rapid charge and discharge with large current, and has excellent stability.
[0236] Fig.12 Graph showing the rate performance of the batteries of Example 1 and Comparative Example 6 of the present invention. Fig.12 It can be seen that the battery in Example 1 of the present invention has a more excellent rate performance.
[0237] Table 1
[0238]
[0239] Table 2
[0240]
[0241] W1 is the mass percentage of the coating layer in the sodium vanadium iron pyrophosphate; Wc is the mass percentage of the carbon element in the sodium vanadium iron pyrophosphate; W B W is the mass percentage of boron in sodium vanadium iron pyrophosphate; N It is the mass percentage of nitrogen in sodium vanadium iron pyrophosphate.
[0242] It can be seen from Table 2 that the battery of the embodiment of the present invention has more excellent discharge specific capacity, average operating voltage, cycle performance and rate performance, indicating that the present invention can effectively improve the electrochemical performance of the battery by designing the composition and structure of sodium iron vanadium phosphate pyrophosphate;
[0243] Further, it can be seen from Examples 1-3 and Example 6 that by selecting the unit cell parameters of sodium vanadium iron pyrophosphate and the mass percentage of nitrogen in the sodium vanadium iron pyrophosphate, the discharge specific capacity, average operating voltage, cycle performance and rate performance of the battery can be further improved;
[0244] It can be seen from Example 1 and Example 7 that by selecting the porosity of sodium vanadium iron pyrophosphate, the discharge specific capacity, average operating voltage, cycle performance and rate performance of the battery can be further improved;
[0245] It can be seen from Example 1, Example 8 and Example 10 that by selecting the content of the coating layer in the sodium vanadium iron phosphate, the discharge specific capacity, average operating voltage, cycle performance and rate performance of the battery can be further improved; further, it can be seen from Example 8 and Example 10 that by further selecting the content of the carbon element, nitrogen element and boron element in the sodium vanadium iron phosphate pyrophosphate, the discharge specific capacity, average operating voltage, cycle performance and rate performance of the battery can be further improved;
[0246] It can be seen from Examples 1 and 9 that when the particle size of the secondary particles of sodium vanadium iron pyrophosphate meets a specific range, the sodium vanadium iron pyrophosphate can improve the battery's discharge specific capacity, average operating voltage, cycle performance and rate performance when applied to the battery.
[0247] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A sodium vanadium iron phosphate pyrophosphate, characterized in that The sodium vanadium iron phosphate pyrophosphate comprises a core and a coating layer coated on at least a portion of the surface of the core; The molecular formula of the core is shown in Formula 1; Na (10+6x) / 3 Fe (7-3x) / 3 V 2x (PO4) (6x+4) / 3 (P2O7) Formula 1; Where x≥0.25; The coating layer includes carbon, boron and nitrogen.
2. The sodium vanadium iron phosphate pyrophosphate according to claim 1, characterized in that In the unit cell of the sodium vanadium iron phosphate pyrophosphate, the length of the a-axis is The length of the b axis is The length of the c-axis is 3. The sodium vanadium iron phosphate pyrophosphate according to claim 1 or 2, characterized in that In the sodium vanadium iron phosphate pyrophosphate, the mass percentage of the coating layer is 1.0-3.0wt%; and / or, In the sodium ferrovanadium phosphate pyrophosphate, the mass percentage of carbon element is 1.0-2.8wt%, the mass percentage of boron element is 0.01-0.05wt%, and the mass percentage of nitrogen element is 0.2-1.2wt%.
4. The sodium vanadium iron phosphate pyrophosphate according to any one of claims 1 to 3, characterized in that The D50 of the secondary particles of sodium ferrovanadium phosphate pyrophosphate is 2-6 μm; and / or, The primary particles of the sodium ferrovanadium phosphate pyrophosphate have a particle size of 50-550 nm; and / or, The particle size distribution of the secondary particles of the sodium ferrovanadium phosphate pyrophosphate is 1.5-4.
0.
5. The sodium vanadium iron phosphate pyrophosphate according to any one of claims 1 to 4, characterized in that In the sodium vanadium iron phosphate pyrophosphate, the thickness of the coating layer is 1-5 nm; and / or, The particle size of the core is 50-500nm.
6. The sodium vanadium iron phosphate pyrophosphate according to any one of claims 1 to 5, characterized in that The porosity of the sodium vanadium iron phosphate pyrophosphate is 5-11%.
7. The sodium vanadium iron phosphate pyrophosphate according to any one of claims 1 to 6, characterized in that The compacted density of the sodium vanadium iron phosphate pyrophosphate is 1.8-2.1 g / cm 3 and / or, The specific surface area of the sodium vanadium iron phosphate pyrophosphate is 4-15m 2 / g.
8. A method for preparing sodium vanadium iron phosphate pyrophosphate according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw material system including a sodium source, an iron source, a vanadium source, a phosphorus source, and a carbon source is sequentially subjected to a spray drying process and a first sintering process to obtain an intermediate material; The intermediate material, the nitrogen source and the boron source are subjected to ball milling treatment and a second sintering treatment to obtain sodium vanadium iron pyrophosphate.
9. The preparation method according to claim 8, characterized in that: The raw material system further includes a dispersant, and the dispersant includes polyvinyl alcohol; and / or, The carbon source is polyvinyl pyrrolidone.
10. The preparation method according to any one of claims 8 to 9, characterized in that: In the spray drying process, the inlet temperature is 175-195°C, the outlet temperature is 90-95°C, and the flow rate is 20-40 mL / min; and / or, In the ball milling process, the ball-to-material ratio is (10-100): (1-5), the rotation speed is 250-500 r / min, and the time is 3-8 h.
11. The preparation method according to any one of claims 8 to 10, characterized in that: In the first sintering treatment, the temperature is 300-400° C. and the time is 2-4 hours; and / or, And / or, in the second sintering treatment, the temperature is 500-550° C. and the time is 8-16 hours.
12. A battery, characterized in that: The invention comprises the sodium vanadium iron phosphate pyrophosphate as described in any one of claims 1 to 7.
Citation Information
Cited By
Method for preparing manganese iron vanadium sodium phosphate by recovering lithium manganese iron phosphate
CN120817587A
Positive electrode material, and preparation method therefor and use thereof
WO2026144109A1
